Cognitions and physical impairments in relation to upper limb function in women with pain and myofascial dysfunctions in the late stage after breast cancer surgery: an exploratory cross-sectional study. Issue 18 (28th August 2022) - De Baets, Liesbet; Devoogdt, Nele; Haenen, Vincent; Evenepoel, Margaux; Dams, Lore; Smeets, Ann; Neven, Patrick; Geraerts, Inge; De Vrieze, Tessa; De Groef, An
Abstract: Purpose: Upper limb (UL) function is one of the health outcomes that matters the most for women with breast cancer. However, a better understanding of the factors contributing to UL dysfunctions in the late stage after breast cancer surgery is needed. This study explores associations between impairment-related and cognition-related factors and UL function in women with pain and myofascial dysfunctions at the affected UL region in this late stage after breast cancer surgery. Methods: In forty-one women, UL function (dependent variable) was evaluated by the Disabilities of Arm, Shoulder and Hand questionnaire. As independent impairment-related factors, relative excessive arm volume (perimetry), pain intensity (maximum score on the visual analogue scale past week) and humerothoracic elevation and scapular lateral rotation (kinematic analysis) were assessed. As independent cognition-related factors, pain catastrophizing (Pain Catastrophizing Scale) and pain hypervigilance (Pain Vigilance and Awareness Questionnaire) were evaluated. Bi-variable analyses and a stepwise regression analysis were used to explore associations. Results: A higher pain intensity ( r = 0.52; p < 0.001), more pain catastrophizing ( r = 0.49; p < 0.001) and more pain hypervigilance ( r = 0.40; p = 0.01) were related to more UL dysfunction. Pain intensity ( p = 0.029) and pain catastrophizing ( p = 0.027) explained furthermore 29.9% of variance in UL function. Conclusions: Pain intensity and cognition-related factors are significantly associated with UL function in women with pain and myofascial dysfunctions, indicating the need of assessing pain beliefs in women in the late stage after breast cancer surgery. IMPLICATIONS FOR REHABILITATION: Pain intensity and pain-related beliefs, including pain attention and catastrophizing, are related to the severity of upper limb dysfunctions in the late stage after breast cancer surgery. Impairments such as lymphedema and movement restrictions seem not related to upper limb function in the assessed sample. To understand upper limb dysfunctions in the late stage after breast cancer, assessing pain beliefs is needed.